(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Terpios hoshinota is a cyanosponge encrusted on the substrate in coral reefs that may cause mass mortality on the infested corals. This research was conducted to investigate the magnitude of damage level of corals due to the T. hoshinota outbreaks by assessing its growth rate, spatiotemporal variation, and prevalence between two sites in Seribu Islands. Four-time observation (T0-T3) in over 18 months (2016-2017) was conducted to see the growth level of sponge using a permanently quadratic photo transect method of 5x5 m (250.000cm2). The total coverage area of sponge on study site in the T0 was 65.252cm2 and becomes 81.066cm2 in T3. The highest level occurred on T2 of 2.051cm2/months in Dapur Island (the closest to Jakarta) and 483cm2/months in the Belanda Island (the further site). The highest sponge growth rate occurred on T1-T2 during transitional season from rainy to dry. The lowest growth rate was observed on T3 during transitional season from dry to rainy. In general, prevalence percentage was higher in Belanda Island than in Dapur Island. This study showed a persistence invasion of encrusting T. hoshinota on coral reef ecosystem that may overcome the function and role of associated organisms.